Commonwealth Caribbean legal literature : supplement 1986-1995 - Newton, Velma (Faculty of Law Library. UWI Cave HillBB, 1995)
Contains listings of current revised editions of laws, law reports, periodicals, bibliographies, articles, monographs and theses on Commonwealth law and law related subjects published in or for the region between 1986-1995.